Pembuatan Material Sandwich Panel Sebagai Pengganti Konstruksi Geladak Kapal Kayu di Wilayah Madura - Iswidodo, Windra (Journal of Applied Civil Engineering and Infrastructure Technology, 2022)
Sandwich panels are a combination of two wooden plates separated by a core. The benefits of using this specimen are still not maximized, only limited to non-structural use in the manufacture of wooden ships. The purpose of this study was to determine the characteristics of sandwich panel specimens using the casting method and the hand layup method. The results of the density test of the casting method have a better value with a value of 1.11 grams/cm³ while pure wood has a density value of 1.21 grams/cm³. The bending strength results from the hand layup method have a better value with a value of 1299.7 N/mm² while pure wood has a bending strength value of 619.7 N/mm². This study concludes that sandwich panel specimens can replace pure wood.